2019
DOI: 10.1080/0144929x.2019.1622786
|View full text |Cite
|
Sign up to set email alerts
|

Older adults’ use of mobile device: usability challenges while navigating various interfaces

Abstract: Mobile devices are becoming ubiquitous among older adults, but have also caused unprecedented challenges due to the high demands of interaction techniques and changeable design patterns found across various applications.This paper aims to investigate how older adults navigate with mobile interfaces and identify their potential usability challenges while navigating. To do so, we summarised six state-of-the-art mobile interface design patterns and conducted individual usability test and in-depth interview with 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 78 publications
1
29
0
Order By: Relevance
“…" ii. Navigation issues: The choice of navigation components or controls within an app can affect ease of use [37], [38]. In other words, users with decreased cognitive capabilities will find it difficult to identify which controls (such as menus or buttons) will take them to the desired location.…”
Section: ) Usability Issuesmentioning
confidence: 99%
“…" ii. Navigation issues: The choice of navigation components or controls within an app can affect ease of use [37], [38]. In other words, users with decreased cognitive capabilities will find it difficult to identify which controls (such as menus or buttons) will take them to the desired location.…”
Section: ) Usability Issuesmentioning
confidence: 99%
“…However, our study identified desirability should be considered before usability for engaging older adults. Whereas usability influence user’s ability to complete a task [ 61 ], desirability means they have a pleasurable and engaging experience while using the system. Initial Engagement will increase when older adults have specific reasons or motivation to use interactive technology for having fun and engaging experiences.…”
Section: New Initial Engagement Values Emerging From Our Case Studmentioning
confidence: 99%
“…Use a one-level (flat) structure due to the difficulty of understanding hierarchical menus [41][42] [43].…”
Section: Menusmentioning
confidence: 99%
“…Use meaningful icons and symbols [15]. Display all menu items at once instead of requiring an additional action to explore more items [43]. Use borders and spaces to illustrate the different items in the interface [15][40].…”
Section: Perceptionmentioning
confidence: 99%